ANALISIS FAKTOR PENENTU KEBIJAKAN DIVIDEN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2008-2012 - DWI RENDRA GRAHA, ERFAN Rendra (Jurnal Akuntansi AKUNESA, 2014)
Dividends are payments made by the company to shareholders, either in the form of cash or stock. Payment of dividends to shareholders showed capital income directly and indirectly invested by shareholders in the company. This study aims to determine what are the factors could affect dividend policy. The sample of this study are companies that listed in the Indonesian Stock Exchange and continuously distribute dividend from  2008 to 2012. The number of samples are 60 companies with number of observations are 300 items. This study using profitability variable, leverage, cash flow, growth, taxes and market ratio with using multiple linear regression on IBM SPPS 20. The results showed that leverage variable and ratio of the market affect dividend policy. However, profitability variable, cash flow, growth, and the tax have no effect on dividend policy   Keyword :Dividend Policy, Leverage, Ratio of the Market